Factors affecting students' interest in learning Islamic education : a case study in a selected secondary school in the district of Gombak - Zaiton Mustafa (Institute of Education, International Islamic University Malaysia, 2010)
This phenomenological case study is carried out to discover the factors that influence students' interest in learning Islamic education subject. Specifically, this qualitative study seeks to answer three main inquiries, namely: (1) what are the major factors that affect students' interest in learning Islamic education subject? (2) how do the students perceive the role of Islamic education subject in helping them to understand the teachings of Islam? And finally, (3) what are the efforts that can be done to increase students' interest in learning Islamic education subject? Data was gathered through an in-depth semi-structured interview conducted with six Form Four students from the selected secondary school in the district of Gombak. From the findings, it was revealed that there are two kinds of factors affecting students' interest in learning Islamic education namely; individual factors and situational factors. The individual factors are; (1) initial interest that resides within each individual and, (2) learner diversity in learning, whereas the situational factors are; (1) parents' influence, (2) Islamic education teacher's influence and, (3) Islamic education curriculum. The findings also revealed that Islamic education teacher is the key factor in affecting students' interest towards the subject. Regarding students' perception towards the role of Islamic education subject, it was found that they have positive perception and realize the importance of learning the subject in their life. Several suggestions have been recommended by the students to improve the teaching practices of Islamic education in our schools. Generally, this study provides useful insights that can be benefitted by those who involve in the field of Islamic education to enhance the teaching and learning process of Islamic education in our educational system.